2016
DOI: 10.20944/preprints201608.0122.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of Life and Poor Oral Health: A Comparison of Postmenopausal Women

Abstract: Abstract:Interrelationships between traditional dental variables are becoming more evident in far reaching aspects of life such as psychosocial interaction, self-esteem, overall health and even occupational performance. This study compares quality of life (QoL) in postmenopausal women (PMW) with poor oral health (POH) with QoL in PMW with good oral health. 200 randomly recruited PMW received a dental evaluation and completed Utian Quality of Life Survey. The participants were divided into POH and healthy group… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…exercise) upon the quality of life scores [ 45 ]. Although oral health-related quality of life is a widely studied subject in the general population [ 46 , 47 ] and also in postmenopausal women [ 48 , 49 ], to the best of our knowledge no previous study used the WHQ to assess the link between the quality of life scores and periodontal health. Premenopausal women may also be susceptible to depressive mood at times of hormonal transitions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…exercise) upon the quality of life scores [ 45 ]. Although oral health-related quality of life is a widely studied subject in the general population [ 46 , 47 ] and also in postmenopausal women [ 48 , 49 ], to the best of our knowledge no previous study used the WHQ to assess the link between the quality of life scores and periodontal health. Premenopausal women may also be susceptible to depressive mood at times of hormonal transitions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that, compared to the scores obtained in the healthy control group, the sexual test scores were lower in each study group with abnormal scores of PPD, CAL, and PI, all of which were the parameters used in diagnosing periodontitis (DeBaz et al., 2015). In another survey study published in 2016, it was reported that postmenopausal women with poor oral health had significantly low sexual test scores (Williams et al., 2016). However, those studies provided limited information about the severity and clinical subtypes of sexual dysfunction (DeBaz et al., 2015; Williams et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In another survey study published in 2016, it was reported that postmenopausal women with poor oral health had significantly low sexual test scores (Williams et al., 2016). However, those studies provided limited information about the severity and clinical subtypes of sexual dysfunction (DeBaz et al., 2015; Williams et al., 2016). They investigated the quality of sexual life in women with periodontitis by using only the three respective items of the general quality of life scale (Utian et al., 2018).…”
Section: Discussionmentioning
confidence: 99%